AGE CHARACTERISTICS IN THE PHYSICAL DEVELOPMENT OF ARTISTIC GYMNASTS - Seytbekova Zulfiya Reymbek qizi (Proximus Journal Publishing, 2024)
In the article, the issues of age characteristics in the physical development of rhythmic gymnasts are comprehensively studied. Every piece of information has been scientifically analyzed.
Keywords: Artistic gymnasts; training; force reaction